2017
DOI: 10.3390/app7121275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Intensity Continuous Ultrasound (LICU) on Mouse Pancreatic Tumor Explants

Abstract: This paper describes the effects of low intensity continuous ultrasound (LICU) on the inflammatory response of mouse pancreatic tumor explants. While there are many reports focusing on the application of low-intensity pulsed ultrasound (LIPUS) on cell cultures and tissues, the effects of continuous oscillations on biological tissues have never been investigated. Here we present an exploratory study of the effects induced by LICU on mouse pancreatic tumor explants. We show that LICU causes significant upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Several studies have suggested increased tissue repair owing to ultrasound exposure [8,9], which has led to the increased use of ultrasound equipment when treating bone fracture [10]. However, the acoustic setups of these [8][9][10] and other [11][12][13][14] tissue-repair studies have been such that thermal effects could not be ruled out. In fact, heating is the most plausible explanation for the phenomena observed [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested increased tissue repair owing to ultrasound exposure [8,9], which has led to the increased use of ultrasound equipment when treating bone fracture [10]. However, the acoustic setups of these [8][9][10] and other [11][12][13][14] tissue-repair studies have been such that thermal effects could not be ruled out. In fact, heating is the most plausible explanation for the phenomena observed [15].…”
Section: Introductionmentioning
confidence: 99%
“…62 Subsequent studies performed in vitro and in vivo, have shown that US at specific wave amplitudes and dose conditions induce cell death in different types of tumors, including leukemia, squamous cell carcinoma and sarcoma under certain acoustic conditions. [27][28][29][30][31][32][33][34] After exposure to US, cells show more classic morphological and molecular features of apoptosis, such as condensation of the nucleus, changes in chromatin position and increased expression of membrane phosphatidylserine. Furthermore, there are changes in the expression of apoptotic BCL-2, such as BAX, BAD and Bak, which promotes the activation of the mitochondrial intrinsic apoptotic pathway releasing cytochrome C to the cytosol, resulting in the activation of caspases 3 and 9.…”
Section: Effects Of Ultrasounds On Gene Expression and Apoptosismentioning
confidence: 99%
“… 20 , 22 , 28 Some studies reported mechanical angiogenesis enhancement. 29 , 30 The effects of low-intensity continuous ultrasounds (LICUS) were studied in a recent paper 31 on the inflammatory response of mouse pancreatic tumor explants. The authors found significant upregulation of IFN-γ, IL-1β and TNF-α in the pancreatic tumor explants.…”
Section: Introductionmentioning
confidence: 99%
“…We are currently developing novel devices to study the biological effects of low intensity ultrasounds in various types of tumor models, including bioprinted 3D tumor & stroma models. Furthermore, we are developing high-resolution ultrasonic methods for a non-invasive early detection of very small physical changes in tissues related with tumor development such as spatial, thermal and elastic properties [22].…”
Section: Crimson Publishersmentioning
confidence: 99%